All-Textile On-Body Antenna for Military Applications - Celenk, Esra; Tokan, Nurhan Turker (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
An all-textile cavity-backed substrate integrated waveguide (SIW) antenna is proposed for military applications. The antenna matches standard military badge size. The aircraft-shape badge antenna that operates in X-band is designed for air force. SIW cavity and meandered slots that form the body and wing of the figure provide resonance at 8 GHz with 26% bandwidth. Symmetrical boresight patterns with very low sidelobes are observed. The measured gain and efficiency of the structure are 5.2 dBi and 79.2% at 8 GHz, respectively. This efficiency value is the highest among other SIW cavity textile-antennas. The antenna is investigated on conformal surfaces, as well. Bending of the antenna to follow body movements does not deteriorate performance of the textile antenna sensor. The peak specific absorption rate value over 10 g of tissue was 0.53 and 0.69 W/kg for 30 dBm input power for female and male breasts, which makes it suitable as an on-body antenna. The badge antenna is fabricated with standard textile fabrication techniques and its simulation performance is confirmed successfully by measurements. Usage of standard off-the-shelf parts for the assembly and fabrication with standard textile fabrication techniques enables simple and cost-effective mass production of the proposed badge antenna.
Keywords: Antennas; Antenna measurements; Textiles; Military aircraft; Slot antennas; Substrates; Fabrication; All-textile; badge antenna; cavity-backed substrate integrated waveguide (SIW); specific absorption rate (SAR); textile antenna; wireless body area network (WBAN); X-band; DESIGN; ARRAY; Engineering; Telecommunications